Registration of 'CP 07‐2137' Sugarcane. Issue 3 (14th June 2016) - Sandhu, Hardev; McCord, Per; Comstock, Jack; Edmé, Serge; Zhao, Duli; Singh, Maninder; Davidson, Wayne; Sood, Sushma; Glynn, Neil; Gilbert, Robert; Gordon, Vanessa; Baltazar, Miguel; et al.
Abstract : 'CP 07‐2137' (Reg. No. CV‐167, PI 676024) sugarcane (a complex hybrid of Saccharum spp.) was released in September 2014 to be cultivated on sandy soils (Entisols) in Florida. CP 07‐2137 was developed through a collaborative cultivar development program of the USDA‐ARS, the University of Florida, and the Florida Sugarcane League, Inc. based at Canal Point (CP), FL. The female parent of CP 07‐2137 is CP 01‐2390, a promising experimental clone on sand that was not released commercially due to its susceptibility to smut disease (caused by Sporisorium scitamineum ). The male parent is a commercial sugarcane cultivar CP 84‐1198, cultivated on both muck (Histosols) and sand. CP 07‐2137 was released due to its significantly greater cane yield, sucrose yield, and economic index than the reference check ('CP 78‐1628'), which is continuously to be the most favorable CP cultivar on sand for last several years. Overall mean cane yield, sucrose yield and economic index in CP 07‐2137 were 37, 44, and 45% greater than CP 78‐1628, respectively. CP 07‐2137 is also resistant to orange rust [caused by Puccinia kuehnii (Kruger) E. Butler] and leaf scald [caused by Xanthomonas albilineans (Ashby) Dowson] diseases. Although the Bru 1 gene (brown rust resistance gene) was absent, CP 07‐2137 is moderately resistant to brown rust (caused by P. melanocephala Syd. & P. Syd.). CP 07‐2137 had poor freeze tolerance, ranking 48th in plant cane and 40th in first ratoon among 54 genotypes tested for their deterioration in sucrose content after exposure to freezing temperatures.